The Effects of a Free Universal After-School Program on Child Academic Outcomes - Nina Drange; Astrid Marie Jorde Sandsør (Center for Economic Studies and ifo Institute (CESifo), 2023)
Studies have shown that a lack of adult supervision of school-aged children is associated with antisocial behavior and poor school performance. To mitigate this, one policy response is to provide structured, adult-supervised programs offered after school throughout the academic year. After-school programs in Norway are an integrated part of school, used to extend the school day to a full working day by providing care before and after school. Participation is voluntary and is subject to fees paid by parents. In the past decade, the quality and content of these programs and the role they can play in integrating children have been under scrutiny. In 2016/17, the city of Oslo gradually introduced and expanded an offer of free part time participation in its after-school program, starting with city districts with a high share of children with an immigrant background. We utilize the staggered roll out of this free after-school program to investigate enrollment, learning outcomes and student wellbeing. The take-up was substantial, raising enrollment rates rates from about 70 to 95% in the first wave of affected schools. However, our difference-in-differences estimates show little overall effect of the program on academic performance, neither on average nor across subgroups. There is also little evidence that the program enhanced student well-being or decreased bullying and we find no evidence of increased maternal labor supply.
Keywords: I21; I24; J13; 330; after-school program; after-school care; difference-in-differences